An analysis of adaptation of the Loanwords in Kikuyu technological Words - NYAGUTHII, GACHAU ELENA; ONG’ONDA, ANASHIA NANCY (International Journal for Innovation Education and Research, 2018)
This paper examines loanwords adopted by native Gikuyu speakers to nativise English technological words using the theoretical framework of Optimality Theory as initiated by Prince and Smolensky (1993). Loanword adaptation is a linguistic phenomenon that occurs cross linguistically whenever one language interacts with another language. However, there are stipulations to borrowing because loanwords must be adapted to fit the second language’s Phonology system. Drawing from a sample of 80 words collected from the domain of technology, medicine, education and agriculture, the study found that Gikuyu speakers use processes such as insertion, deletion, vowel substitution and preservation to nativist borrowed word from English. The study also found out that this process occurs because of the tolerance threshold to segment preservation within a given constraint domain and due to distinctive features in English language and Gikuyu language.